(untitled) (Biological Sciences - PJSIR, 1995)
Currently used post-harvest applied commercial formulations of potato sprout inhibitors show a degree of effectiveness at relatively low temperatures of 8 - lO°e. Attempts have already been made to store potato tubers at around 24°C with sprout suppressant [1].